Bioaccumulation of arsenic and immunotoxic effect in white shrimp (Penaeus vannamei) exposed to trivalent arsenic. Issue 122 (March 2022) - Liao, Zhen-Hao; Chuang, Hsiang-Chieh; Huang, Huai-Ting; Wang, Pei-Hsuan; Chen, Bo-Ying; Lee, Po-Tsang; Wu, Yu-Sheng; Nan, Fan-Hua
Abstract: Trivalent arsenic (As (III)) contamination in the marine environment can produce adverse effects in crustaceans. The present study investigated the chronic toxicity of As (III) in white shrimp ( Penaeus vannamei) by analyzing the tissue bioaccumulation and non-specific immune responses. Shrimps were exposed to 0 (control), 50, 500, and 2500 μg/L of As (III) for 21 days. The results showed that the hepatopancreas was the main tissue of arsenic accumulation in white shrimp. The cumulative concentration of total arsenic and inorganic arsenic but not arsenobetaine was positively correlated with the exposure concentration. In vitro As (III) treatment (0–2500 μg/L) with haemocytes isolated from healthy shrimp did not cause the cytotoxicity, but this arsenic treatments inhibited the phagocytic rate and O2 − production. Moreover, the decrease of total haemocyte count and the inhibition of phagocytic rate, phagocytic index, O2 − production and phenoloxidase activity were observed in white shrimp under the exposure of As (III) over a period of 21 days. This study revealed that chronic As (III) stress could disturb arsenic metabolism and immune responses in P. vannamei . Highlights: Penaeus vannamei mainly bioaccumulate arsenic in hepatopancreas. Chronic As (III) exposure disturb arsenic metabolism in P. vannamei. Chronic As (III) exposure cause in vitro and in vivo immnotoxicity in P. vannamei. As (III) impair O2 − production, phagocytic and phenoloxidase activity of haemocyte.